Is It Feasible to Use CMV-Specific T-Cell Adoptive Transfer as Treatment Against Infection in SOT Recipients? - García-Ríos, Estéfani; Nuévalos, Marcos; Mancebo, Francisco J.; Pérez-Romero, Pilar (Frontiers in Immunology, 2021)
During the last decade, many studies have demonstrated the role of CMV specific T-cell immune response on controlling CMV replication and dissemination. In fact, it is well stablished that patients lacking CMV-specific T-cell immunity have an increased occurrence of CMV replication episodes in transplanted patients. In this context, the use of adoptive transfer of CMV-specific T cells has been widely investigated and applied to Hematopoietic Stem Cell Transplant patients and may be useful as a therapeutic alternative, to reconstitute the CMV specific T-cell response and to control CMV viremia in patients receiving a transplantation. However, only few authors has explored the use of T cell adoptive transfer in SOT recipients. We propose a novel review in which we provide an overview of the impact of using CMV-specific T cell adoptive transfer on the control of CMV infection in SOT recipients, the different approaches to stimulate, isolate and expand CMV-specific T cells developed over the years and a discussion of the possible use of CMV adoptive cellular therapy in this population. Given the timeliness and importance of this topic, we believe that such an analysis will provide important insights into CMV infection and its treatment/prevention.